2011
DOI: 10.1002/prca.201000153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of subclinical and clinical acute T‐cell‐mediated rejection in renal transplant patients by urinary proteome analysis

Abstract: The established marker set contains peptides related to tubulointerstitial infiltration seen in acute rejection. The set of urinary peptide markers will be used for early diagnosis of acute kidney allograft rejection marker in a multicenter phase III prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 41 publications
0
49
0
1
Order By: Relevance
“…These general characteristics are consistent with the concept that inflammatory mechanisms play an important role in the development of SAKI. MMP8 was previously reported as a candidate biomarker for detecting renal allograft rejection (29). Genetic ablation or pharmacologic inhibition of MMP8 delays renal recovery in mice subjected to renal ischemia (30), which is consistent with the MMP8-based decision node in the model.…”
Section: Discussionmentioning
confidence: 99%
“…These general characteristics are consistent with the concept that inflammatory mechanisms play an important role in the development of SAKI. MMP8 was previously reported as a candidate biomarker for detecting renal allograft rejection (29). Genetic ablation or pharmacologic inhibition of MMP8 delays renal recovery in mice subjected to renal ischemia (30), which is consistent with the MMP8-based decision node in the model.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has also successfully been used in clinical trials in transplant patients 25,26 . The data from one of these studies indicated that urine samples from patients with subclinical acute T-cell-mediated tubule-interstitial rejection could be distinguished from non-rejection controls mainly based on altered collagen α(I) and α (III) chain fragments suggesting an involvement of matrix metalloproteinase-8 (MMP-8) 25 . Nevertheless, this CE-MS proteomics assay has mainly been studied in chronic kidney disease patients and its value specifically for transplant patients still remains to be evaluated.…”
Section: Predictive Biomarkers In Transplantation Based On Non-targetmentioning
confidence: 99%
“…Chronic rejection remains the major limitation of renal transplantation, and circumstantial evidence may indicate a role for MMPs. Numerous studies have collectively identified increases in MMP-2, MMP-7, MMP-8, and MMP-9, as well as TIMP-1 and -2 in cases of allograft rejection (16,27,68,80,104,105,145). Interestingly, polymorphisms in MMP-2 and -9 have been associated with increased allograft survival (116), and the immunosuppressive drug rapamycin inhibits MMP-9 expression while increasing TIMP-1 (94).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%